FONOLOGI BAHASA MINANGKABAU DI KENAGARIAN PADANG LAWEH KABUPATEN SIJUNJUNG - Ella Sumidita; Ermanto Ermanto; Ngusman Ngusman (Faculty of Languages and Arts, Universitas Negeri Padang, 2013)
This article was written based on (1) to describe fonem vocal, consonant, semivocal, diphthongs, (2) distribution of vocals, consonants, semivocal and diphthongs, (3) form syllables of Minangkabau in Padang Laweh. The method used in this research was descriptive method. It is the method that used to describe something in objective situation. The data were collected used pancing technique that has good purpose to a researcher to do it again that the language never studied before in short time to describe collections fact. The finding of this research were Minangkabau language in Padang Laweh has 5 complete distribusy vocal, 14 incomplete consonants, 2 complete distribusi semivocal, 7 incomplete distribution diphthongs and 4 syllables.